Manfaat Teknik Relaksasi Napas Dalam Untuk Menurunkan Kecemasan Pasien Pre Operasi General Anastesi - Hamarno, Rudi; Arif, Taufan; Oktavia, Devi Ayu; Supono (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Introduction: Preoperative patients with anxiety will cause an increase in breathing frequency and heart rate, potentially resulting in the cancellation of surgery. Anxious patients will be intervened through deep breath relaxation techniques that are proven to reduce anxiety levels. Method: The research design is